The study on effect of accelerated aging and gibberellic acid on germination characteristics, lipids peroxidation, soluble protein, total phenol and electrical conductivity of wheat seed (Pishtaz Cultivar) (Triticum aestivum L.) - zahra Mohaddes Ardebili; Hossein Abbaspour; Reza Tavakkol afshari; Seid Mohsen Nabavi Kalat4 (علوم و فناوری بذر ایران)
In order to study the effect of accelerated aging and priming with gibberellic acid on germination characteristics, lipids peroxidation, soluble protein, total phenol and electrical conductivity of wheat seed (Pishtaz Cultivar) an experiment in factorial laid out completely randomized design with three replications was conducted at Seed Technology Laboratory, Department of Agronomy, Faculty of Agriculture, Ferdowsi University, Mashhad, Iran, in 2016. Factors were included of seed aging(100% relative humidity at 40°C) in three levels [low deterioration (4 days), medium deterioration (6 days) and high deterioration (7 days)] and priming with gibberellic acid in four levels (0, 25, 50 and 100 ppm). Analysis of variance showed that the effect of seed aging, priming with gibberellic acid and interaction between two factors on all traits were significant. Based on the means comparison of the traits germination percentage, germination rate, soluble protein and total phenol decreased with increasing aging time. But, the level of malondyaldeid and electrical conductivity increased due to damage to cell membrane with increasing aging time. Investigation of interaction between two factors showed that the priming with gibberellic acid reduced the negative effects of seed aging on all traits.